Fusobacterium nucleatum Promotes the Progression of Colorectal Cancer Through Cdk5-Activated Wnt/β-Catenin Signaling - Li, Xiang; Huang, Jiepeng; Yu, Tingting; Fang, Xiaoting; Lou, Liqin; Xin, Shijun; Ji, Ling; Jiang, Feizhao; Lou, Yongliang (Frontiers in Microbiology, 2021)
Background/Aims: Growing evidence supports the direct link of Fusobacterium nucleatum with colorectal cancer (CRC). However, to date, the underlying mechanism of action remains poorly understood. In this study, we examined the effects of F. nucleatumon on the progression of CRC and investigated whether cyclin-dependent kinase 5 (Cdk5) is involved in the effect through activating the Wnt/β-catenin signaling pathway. Materials and Methods: CRC tissues and matched histologically normal specimens were collected from patients who were diagnosed with CRC and underwent surgical treatment in our hospital between January 2018 and January 2019. Two human CRC cell lines, including DLD-1 and SW480, were utilized mainly for in vitro mechanistic investigations. Results: The abundance of F. nucleatum was significantly greater in CRC tissues than in cancer-free specimens, which was significantly correlated with the progression of CRC. In vitro investigations revealed that F. nucleatum significantly enhanced the proliferation and migration of CRC cells. Furthermore, F. nucleatum significantly induced the expression of Cdk5 and activation of the Wnt/β-catenin signaling pathway. Notably, knockdown of Cdk5 significantly abrogated the effects of F. nucleatum on cellular processes and Wnt/β-catenin signaling in relation to the progression of CRC. Conclusions: The results of this study demonstrate that F. nucleatum orchestrates a molecular network involving the direct role of Cdk5 in activating Wnt/β-catenin signaling to modulate CRC progression. Thus, in-depth investigations of F. nucleatum-associated molecular pathways may offer valuable insight into the pathogenesis of CRC, which may help further the development of treatment for this disease.